"Moving like a boxer" : a study of Cape Town's boxing youth - Sender, Simon (Social Anthropology, 2016)
This thesis attempts to investigate the topic of 'community' boxing gyms in the city of Cape Town. Broadly, it asks the question: what is it about boxing (and particularly boxing) that seems to dictate its co-occurrence with scenarios of social precarity? To answer this question, the study uses ethnographic methods to consider questions of socio-political history, precarity, embodiment, structural violence and physical violence. In the final analysis, the thesis argues for the clear benefit of having community boxing gyms in South African informal settlements or other typically violent locales. Research was conducted at two boxing gyms in the Greater Cape Town area.